A laboratory model of Saturn's North Polar Hexagon - Aguiar, A; Read, P; Wordsworth, R; Salter, T; Yamazaki, Y (2010)
A hexagonal structure has been observed at ∼76°N on Saturn since the 1980s (Godfrey, D.A. [1988]. Icarus 76, 335-356). Recent images by Cassini (Baines, K., Momary, T., Roos-Serote, M., Atreya, S., Brown, R., Buratti, B., Clark, R., Nicholson, P. [2007]. Geophys. Res. Abstr. 9, 02109; Baines, K., Momary, T., Fletcher, L., Kim, J., Showman, A., Atreya, S., Brown, R., Buratti, B., Clark, R., Nicholson, P. [2009]. Geophys. Res. Abstr. 11, 3375) have shown that the feature is still visible and largely unchanged. Its long lifespan and geometry has puzzled the planetary physics community for many years and its origin remains unclear. The measured rotation rate of the hexagon may be very close to that of the interior of the planet (Godfrey, D.A. [1990]. Science 247, 1206-1208; Caldwell, J., Hua, X., Turgeon, B., Westphal, J.A., Barnet, C.D. [1993]. Science 206, 326-329; Sánchez-Lavega, A., Lecacheux, J., Colas, F., Laques, P. [1993]. Science 260, 329-332), leading to earlier interpretations of the pattern as a stationary planetary wave, continuously forced by a nearby vortex (Allison, M., Godfrey, D.A., Beebe, R.F. [1990]. Science 247, 1061-1063). Here we present an alternative explanation, based on an analysis of both spacecraft observations of Saturn and observations from laboratory experiments where the instability of quasi-geostrophic barotropic (vertically uniform) jets and shear layers is studied. We also present results from a barotropic linear instability analysis of the saturnian zonal wind profile, which are consistent with the presence of the hexagon in the North Pole and absence of its counter-part in the South Pole. We propose that Saturn's long-lived polygonal structures correspond to wavemodes caused by the nonlinear equilibration of barotropically unstable zonal jets. © 2009 Elsevier Inc. All rights reserved.